ANALISIS KUALITATIF FORMALIN PADA TAHU MENTAH YANG DIJUAL DI PASAR KALINDO, TELUK TIRAM DAN TELAWANG BANJARMASIN - Novia Ariani; Maida Safutri; Siska Musiam (Jurnal Ilmiah Manuntung, 2016)
Tofu is one of favourite food in Indonesia because it is containing the nutrients which body needs, such as protein. Tofu comes from processed soybeans and contains high water, so it can only save for 1 or 2 days in storage. Because of that reason several   manufacturers or dealers add additional ingredients, one of them was formaldehyde to made tofu were durable to be restored and increases consumer appeal. The aim of the study was to identifity the contain of formaldehyde at crude tofu in Kalindo, Teluk Tiram and Telawang market Banjarmasin. The investigated sample was white crude tofu were 19 samples obtained with accidental sampling. The type of research was descriptive research. Qualitative analysis of formaldehyde at crude tofu was done with conventional method by using Ag(NH3)2NO3 and KMnO4 0,1N reagents. The result of study shows that crude tofu was sold in Kalindo market 90% (9 of 10 samples) positive contain formaldehyde, 100% (4 of 4 samples) at Teluk Tiram market positive contain formaldehyde and 80% (4 of 5 samples) at Telawang market positive contain formaldehyde